Level of Sulfite Oxidase Activity Affects Sulfur and Carbon Metabolism in Arabidopsis - Oshanova, Dinara; Kurmanbayeva, Assylay; Bekturova, Aizat; Soltabayeva, Aigerim; Nurbekova, Zhadyrassyn; Standing, Dominic; Dubey, Arvind Kumar; Sagi, Moshe (Frontiers in Plant Science, 2021)
Molybdenum cofactor containing sulfite oxidase (SO) enzyme has been shown to be an important player in protecting plants against exogenous toxic sulfite. It was also demonstrated that SO activity is essential to cope with rising dark-induced endogenous sulfite levels and to maintain optimal carbon and sulfur metabolism in tomato plants exposed to extended dark stress. The response of SO and SiR to direct exposure of low and high levels of sulfate and carbon was rarely shown. By employing Arabidopsis wild-type, sulfite reductase (SiR) and SO modulated plants supplied with excess or limited carbon or sulfur supply, the current study demonstrates the important role of SO in carbon and sulfur metabolism. Application of low and excess sucrose, or sulfate levels, led to lower biomass accumulation rates, followed by enhanced sulfite accumulation in SO impaired mutant compared to wild-type. SO-impairment resulted in the channeling of sulfite to the sulfate reduction pathway, resulting in overflow of organic S accumulation. In addition, sulfite enhancement was followed by oxidative stress contributing as well to the lower biomass accumulation in SO modulated plants. These results indicate that the role of SO is not limited to protection against elevated sulfite toxicity, but to maintaining optimal carbon and sulfur metabolism in Arabidopsis plants.